THE EFFECT OF SPIRITUALITY ON THE SYNDROME OF BURN OUT AND NURSE TURNOVER INTENTION AT THE ISLAMIC HOSPITAL OF GONDANGLEGI MALANG - Hari Dwi Suharsono; Nikma Fitriasari; Anggi Gilang Yudiansyah; Faritz Subiyaktoro Putra (Department of Nursing, Faculty of Health Sciencce, Universitas Brawijaya, 2019)
Nurse spirituality is the effort of nurses to find the highest meaning of work life in the hospital and communicate between individuals and coworkers. Nurse spirituality has three dimensions, namely inner life, meaningful work and belonging in the community. These three dimensions will facilitate the nurse to create a feeling of prosperity and fun while working. This will affect burn out syndrome and turnover intention. The purpose of this study was to determine the effect of spirituality on the syndrome of burn out and nurse turnover intention at the Islamic Hospital of Gondanglegi Malang.The method used is a quantitative with cross sectional design and Partial Least Square(PLS) approach. The population in this study were all nurses who worked at the Islamic Hospital of Gondanglegi Malang and we used total sampling to obtain the respondents. We collect data used questionnaire in 118 nurses on September 2018.The results showed that spirituality had a negativeand significant effect on the occurrence of burn out with a path coefficient value of -0.448 and t-statistic of 8.674 (t-statistic > 1,96). There is a negative and significant influence of spirituality on turnover intention with a path coefficient value of -0.174 and t-statistic of 2.526. There is a positive and significant effect of burn out on turnover intention with a path coefficient value of 0.608 and t-statistic of 9.183. In conclusions there were a significant effect of spirituality on burn out syndrome and nurse turnover intention at the Islamic Hospital of Gondanglegi Malang. This study illustrates that the higher the nurse’s spirituality in the hospital will reduce theoccurrence of burn out and turnover intention.